2014
DOI: 10.3390/s140916467
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Eye Fatigue Caused by 3D Displays Based on Multimodal Measurements

Abstract: With the development of 3D displays, user's eye fatigue has been an important issue when viewing these displays. There have been previous studies conducted on eye fatigue related to 3D display use, however, most of these have employed a limited number of modalities for measurements, such as electroencephalograms (EEGs), biomedical signals, and eye responses. In this paper, we propose a new assessment of eye fatigue related to 3D display use based on multimodal measurements. compared to previous works Our resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 20 publications
0
60
0
Order By: Relevance
“…Numerous studies have been conducted to evaluate the visual fatigue caused because of watching 3D displays using electroencephalogram (EEG) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The EEG method is selected as it is the most significant and reliable physiological measure for evaluating mental fatigue [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted to evaluate the visual fatigue caused because of watching 3D displays using electroencephalogram (EEG) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The EEG method is selected as it is the most significant and reliable physiological measure for evaluating mental fatigue [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…De Waard [22], and Fisch and Spehlmann [23] classified the EEG signal into four characteristic waves based on their frequency, namely delta wave (δ, 0-4 Hz), theta wave (θ, 4-8 Hz), alpha wave (α, [8][9][10][11][12][13], and beta wave (β, 13-30 Hz). The delta (δ) wave is usually related to the depth of sleep; moreover, this wave is associated with specific encephalopathic diseases and underlying lesions [13]. The theta (θ) wave is related to drowsiness.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, eye movements provide valuable insight into overt visual attention in addition to covert attention captured through EEG measurements [13]. Furthermore, eye blink rate is known to relate to visual fatigue [14] and pupil dilation to cognitive load [15], both of which are relevant to QoE assessment. Of practical relevance, the eye measurement may provide insight into cognitive activity that is not easily observable through other methods.…”
Section: Psychophysiology and Qoementioning
confidence: 99%
“…3) Prior art: Previous studies have demonstrated an association between eye BR and visual discomfort [14]. One study examining QoE viewing on 3D displays showed opposite effects on changes in eye BR and visual discomfort based on whether presented stimuli was in-depth motion, which caused an increase in rate, or planar motion, which resulted in a decreased rate [81].…”
Section: Comparable Contributions By Eeg and Eda (Gsr)mentioning
confidence: 99%
See 1 more Smart Citation